Health care of emotional processes and risk in professionals working with human suffering - Morales F., Germán; Pérez E., Janet; Menares N., María Alejandra (Revista de Psicología, 2003)
From the sixties onwards, there exists an increasing interest on the burn-out risk that professionals working with human suffering experience. This paper is about a research carried out in three institutions involved in healing social and physical damage in children and adolescents. A qualitative methodology was used, based on Glasser & Strauss grounded theory. Eight professionals from the mentioned institutions were interviewed. It turned out that all i acknowledged being at mental health risk, displaying some differences in their experiences. Also, all mentioned that sharing experiences in a group conversation was their main strategy for mental self-care.